Customer Engagement in Multi-Sensory Virtual Reality Advertising: The Effect of Sound and Scent Congruence - Brengman, Malaika; Willems, Kim; De Gauquier, Laurens (Frontiers in Psychology, 2022)
Despite the power of VR in immersing viewers in an experience, it generally only targets viewers via visual and auditory cues. Human beings use more senses to gather information, so expectedly, the full potential of this medium is currently not yet tapped. This study contributes in answering two research questions: (1) How can conventional VR ads be enriched by also addressing the forgotten sense of smell?; and (2) Does doing so indeed instill more engaging experiences? A 2x3 between-subjects study (n=235) is conducted, whereby an existing branded VR commercial (Boursin Sensorium Experience) is augmented with ‘sound’ (on/off) and (congruent/incongruent/no) ‘scents’. The power of these sensory augmentations is evaluated by inspecting emotional, cognitive and conative dimensions of customer engagement. The results identify product-scent congruence (with sound) as a deal-maker, albeit product-scent incongruence is not necessarily a deal-breaker. The article concludes with further research avenues and a translation into managerial implications.